2019
DOI: 10.1155/2019/9149203
|View full text |Cite
|
Sign up to set email alerts
|

Acute Exposure to Permethrin Modulates Behavioral Functions, Redox, and Bioenergetics Parameters and Induces DNA Damage and Cell Death in Larval Zebrafish

Abstract: Permethrin (PM) is a synthetic pyrethroid insecticide widely used as domestic repellent. Damage effects to nontarget organisms have been reported, particularly in the early stages of development. Studies indicate redox unbalance as secondary PM effect. Therefore, our goal was to investigate the acute PM effects on larval zebrafish. Larvae (6 days postfertilization) were exposed to PM (25–600 μg/L) during 24 hours, and 50% lethal concentration was estimated. For subsequent assays, the sublethal PM concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 101 publications
(125 reference statements)
1
8
0
Order By: Relevance
“…Indeed, their research has shown that exposure of Delta Smelt larvae to 50 ng/L permethrin and 2 ng/L bifenthrin, for 96 h, resulted in significant hyperactivity, as well as a decrease in thigmotaxis (wall hugging). Similar observations have been reported for Zebrafish larvae exposed to permethrin at 50 μg/L for 24 h, resulting in alterations in nonmotor behavioral patterns, such as decreased defensive behaviors linked to thigmotaxis and scototaxis (dark/light preference) [ 44 ]. Direct links of these effects on survival in the field and overall fitness are difficult to predict, but these behavior alterations are likely to cause changes in ability to avoid predation, capture prey and subsequently affect reproduction success, leading to a decrease in population abundance [ 23 , 49 ].…”
Section: Introductionsupporting
confidence: 80%
See 2 more Smart Citations
“…Indeed, their research has shown that exposure of Delta Smelt larvae to 50 ng/L permethrin and 2 ng/L bifenthrin, for 96 h, resulted in significant hyperactivity, as well as a decrease in thigmotaxis (wall hugging). Similar observations have been reported for Zebrafish larvae exposed to permethrin at 50 μg/L for 24 h, resulting in alterations in nonmotor behavioral patterns, such as decreased defensive behaviors linked to thigmotaxis and scototaxis (dark/light preference) [ 44 ]. Direct links of these effects on survival in the field and overall fitness are difficult to predict, but these behavior alterations are likely to cause changes in ability to avoid predation, capture prey and subsequently affect reproduction success, leading to a decrease in population abundance [ 23 , 49 ].…”
Section: Introductionsupporting
confidence: 80%
“…An increase in the amount of time in the center or open zone, depending on the test, is considered to be reflective of an anxiolytic response to a compound such as caffeine [ 57 ]. Nunes et al (2019) also advanced the hypothesis that permethrin exposure (50 μg/L) may have decreased the anxiety-like behavior in Zebrafish larvae, altering the normal preference of the periphery in favor of the central area [ 44 ]. This change of anxiety related behavior after a pyrethroid exposure may be a threat to the survival of these larvae in terms of predator avoidance and food capture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This increases reactive oxygen species (ROS) production and inhibits mitochondrial complex I. Thus, the deficit of antioxidant enzymes in different organs leads to protein, lipid and DNA damage [25,28,31]. However, there is little information about PERM neurotoxicity after exposure to low doses and for short periods.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that exposure to different permethrin concentrations can alter the function of mitochondria, with the consequent increase in oxidative stress and inflammatory processes [27,28,30]. PERM can adversely affect cognitive and mood function either directly or indirectly via reduced hippocampal neurogenesis [27][28][29][30][31]. In the present study, we evaluated neurotoxicity induced by subacute exposure to PERM in sublethal doses and its effects on the immune systems, bioenergetic redox and morphology of the brain using an animal model.…”
Section: Introductionmentioning
confidence: 98%